Morfologi dan Geometri Morfometri Holthuisana sp. (Crustacea, Decapoda, Gecarcinucidae) dari Danau Sentani, Papua - Rury Eprilurahman; Burhan Amirudien; Trijoko Trijoko (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Holthuisana is a freshwater crab member of the family Gecarcinucidae which has a distribution in eastern Indonesia to Australia. This study was aimed to determine the variations in the shape of carapace and chelae within genus Holthuisana collected from Sentani Lake, Papua using analysis of geometric morphometric. The morphological characters confirmed the specimen examined belong to genus Holthuisana. The results showed that male crabs had slightly larger carapace length and width than females. The length and width of the large chelae in male crabs are greater than that of females. The ratio of carapace length and width to male is 6:5, and female is 5:4. The ratio of the length and width of the chelae (propodus) in male crabs is 9:5, and in females 2:1. Based on the 16 landmarks of carapace, there are no significant different between male and female crabs. Thus, based on 12 landmarks of chelae, the large right cheliped shows different variations between males and females. The large right cheliped of the males shows more convex on polex and propodus compare to the females. The large left cheliped shows variations that are not much different.Key words: freshwater crab; geometric morphometrics; morphological characters; New Guinea